Experimental and numerical study on fatigue performance of U-rib connections. (December 2019) - Chen, Shiming; Huang, Yang; Zhou, Cong; Gu, Ping
Abstract: The welded and bolted splice plate connections in orthotropic steel decks (OSD) are prone to fatigue problems resulting from the high cyclic stresses. An experimental study was conducted to investigate the fatigue behavior of U-rib connections. Four OSD specimens, two with butt-welded connections, and two with bolted splice plate connection were experimentally studied. For the U-rib welded connections, fatigue cracks were first observed on the outside bottom in the connection welds and propagated along the welds in the two side webs of the ribs approaching up to the deck plate. For the bolted splice plate connection, vertical cracks were first observed at the bottom of the inside splice plates. Cracks were then observed on the outside bottom in the connecting plates and propagated upward, and finally separated the splice plate completely. The test results were evaluated and compared to the existing codified S–N curves. The fatigue strengths of two connections are found in the category C of AASHTO (89 MPa) and category 90 MPa of EUROCODE. The finite element models of the U-rib connections were developed and verified by the test results. Parameter analyses were further conducted to investigate the likely influences of the fatigue behavior. For the welded connection, increasing the rib thickness, reducing weld size and adopting smooth weld shape can reduce the stress of butt-welded joints. For the splice plate connection, using thicker and wider splice plates can effectively reduce the fatigue stresses of the joints, hence improve the fatigue strength of this type U-rib connection. Highlights: The fatigue behavior of butt-welded and bolted connections was experimentally investigated. Fatigue failures of two types of connections were found. The welded and bolted connections can be classified as the AASHTO-C and EUROCODE-90MPa. FE analyses and Parameter analyses were conducted to reveal the fatigue-prone details and improve the fatigue performance.